메타버스에서의 디자인보호 -개정 화상디자인 제도의 공백을 감안하여 - 조영선; Cho Youngsun (지식재산연구, 2023)
이 글은 메타버스 환경에서의 디자인권 침해에 대한 대응방법을 개정 디자인법상 화상디자인 제도의 입법적 공백과 연결 지어 검토한다. 메타버스 가상환경이 업무, 학업, 사교 및 각종 여가활동 등 점차 ‘일상생활’을 대체하는 역할을 수행하게 됨에 따라 일상의 디자인물품이나 디자인적 가치가 있는 건축물 등이 가상공간에서 재현되는 일이 많아지고, 동시에 그런 각도에서 디자인권자의 적절한 보호 필요성이 크게 증가하고 있다. 무엇보다, 디자인의 등록 적격을 디지털 이미지 전체로 확장하는 파괴적 변화까지는 피하면서 실물디자인의 권리범위를 가상공간으로 확대하는 방안이 필요하지만, 현행법 아래서는 이를 적절히 규율할 방법이 없다. 현재까지는 저작권법을 적용하거나 부정경쟁방지법의 성과도용행위로 규율하는 등의 해결책이 시도되고 있으나, 법리상 중대한 한계와 문제점들을 내포하고 있다. 결국 이 문제는 법 개정을 통해 해결하는 수밖에 없을 것이고, 이를 위해 디자인보호법을 개정하는 것을 검토할 필요가 있다. 디자인보호법의 개정은 문제를 정면에서 그리고 궁극적으로 해결하는 방법이지만, 기존의 패러다임을 크게 변화시켜야 하고 다른 지적재산권법(특허, 실용신안, 상표 등)과의 정합성도 문제될 수 있으므로 신중한 접근이 필요하다. 이를 위한 충분한 논의와 검토, 그리고 입법적 합의가 이루어질 때까지 임시적 대안으로서, 부정경쟁방지법 제2항 제2호 자.목 ‘상품형태 모방행위’의 상품 개념에 디지털 이미지를 포함하고 전기통신회선을 통해 제공하는 행위태양을 추가함으로써 합리적이고 무난한 해결이 가능할 것으로 생각된다. This article covers legal issues of design protection in metaverse. The discussions in this article also remind regulation deficiency of virtual design in the Design Protection Act. As metaverse rapidly is becoming a platform of daily life: business, study, leisure and social activity, the virtual reproductions of real world designs (hereinafter, “digital copy”) are increasing in parallel. Accordingly, the logic to extend design right protection of real world to digital copies in metaverse has become a pressing concern. However, it is risk-taking to change the whole framework of law to encompass “pure virtual images of imaginary products” as a subject matter of design. In order to provide protection to real world designs against illegal digital copies of them, it is commonly suggested to regulate digital copies of designs without consent as copyright infringement or unfair competition (theft of products of endeavors made by others). As detailed analysis shows all methods have endogenic limitations and theoretical shortage, law making to cope with inappropriate digital copy shall be a fundamental resolution. Although the amendment of the Design Protection Act is a direct and final countermeasure, it entails serious paradigm shifts and conflicts with conventional IP law regulations. To make a prudential access to this task, this article suggests a temporary legislative alternative: the amendment of “Shape-Imitation of Products of Others” clause in the Unfair Competition Act to encompass items related to digital copies. Digital images of products shall be a kind of “shape of goods” and its transfer on the Internet be a new type of exploitation.